Effects of soil texture on microbial community composition and abundance under alternate wetting and drying in paddy soils of central Thailand - Noppol Arunrat; Sukanya Sereenonchai; Toungporn Uttarotai (Scientific Reports)
Abstract Alternate wetting and drying (AWD) in paddy fields creates alternating anoxic and aerobic conditions, significantly influencing soil physical and chemical properties and shaping dynamic microbial communities. This study aimed to compare soil microbial community composition and abundance across different soil textures under similar AWD practices. Four paddy fields with distinct soil textures—silty clay loam, sandy loam, clay loam, and clay—were studied, all managed with the same cultivation practices and two AWD cycles during the growing season. Soil bacterial diversity was assessed using 16 S rRNA gene amplicon sequencing. Results showed that clay soils harbored richer and more diverse microbial communities, with distinct taxonomic compositions compared to other soil types. Methane-related taxa such as Methanosaetaceae, Methanomassiliicoccaceae, and Methanoregulaceae were more abundant in clay soils, along with significantly higher abundances of Methanosaeta, Methanocella, Methanolinea, and Methanoregula at the genus level. Enhancing soil organic matter content was associated with improved properties—including available phosphorus, exchangeable magnesium, cation exchange capacity, and exchangeable calcium—which collectively support greater microbial diversity and abundance across soil textures. This study reveals that clay-rich soils significantly shape microbial communities under AWD and highlights key methanogenic taxa as bioindicators of methane cycling in paddy fields.